2009
DOI: 10.1890/08-0442.1
|View full text |Cite
|
Sign up to set email alerts
|

Managing the impact of invasive species: the value of knowing the density–impact curve

Abstract: Economic impacts of invasive species worldwide are substantial. Management strategies have been incorporated in population models to assess the effectiveness of management for reducing density, with the implicit assumption that economic impact of the invasive species will also decline. The optimal management effort, however, is that which minimizes the sum of both the management and impact costs. The relationship between population density and economic impact (what we call the "density-impact curve") is rarely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
214
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(219 citation statements)
references
References 35 publications
5
214
0
Order By: Relevance
“…managing for a level of invader cover that is least costly to maintain) since economic and biodiversity objectives are essentially concordant. In relation to invasive species population density and economic impact, Yokomizo et al (2009) have argued that the optimal management effort will minimise the sum of both management and impact Goodall and Naudé (1998). Maintenance control, as defined by the authors, is that undertaken at 0-5% infestation cover.…”
Section: Management Strategy Options-eradication Extirpation and Maimentioning
confidence: 99%
“…managing for a level of invader cover that is least costly to maintain) since economic and biodiversity objectives are essentially concordant. In relation to invasive species population density and economic impact, Yokomizo et al (2009) have argued that the optimal management effort will minimise the sum of both management and impact Goodall and Naudé (1998). Maintenance control, as defined by the authors, is that undertaken at 0-5% infestation cover.…”
Section: Management Strategy Options-eradication Extirpation and Maimentioning
confidence: 99%
“…Of the principal determinants of IAS impact (i.e., per capita effect, abundance, and range size; Parker et al 1999, Yokomizo et al 2009, Thomsen et al 2011, per capita effect has heretofore been much more difficult to assess and has largely been quantified using correlations such as native abundances pre-and post-invasion (Parker et al 1999). Our meta-analysis considers consumptive impacts of IAS influenced by both their per capita effects and abundances, as measured from correlative, per capita, and per biomass studies.…”
Section: Temperature As a Mediator Of Impactmentioning
confidence: 99%
“…While FR provides an efficient tool for relative predictions of per capita effect, a more complete measurement of impact would include the abundance of the IAS (Parker et al 1999, Yokomizo et al 2009, Thomsen et al 2011. A meta-analysis on inland water and marine systems revealed that higher abundances of IAS lead to increased ecological impacts across taxonomic groups and feeding strategies (Thomsen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, invasive plant growth has been found to be more suppressed by negative soil feedbacks with time since invasion (Diez et al 2010). Abundance of the invader will also change over time, though the relationship between invader abundance and impact may increase (Thomsen et al 2011) or decrease linearly (Kornis et al 2014), or have a non-linear relationship, depending on the response being measured (Yokomizo et al 2009, Jackson et al 2015. Changes in impacts over time are not well understood as most impact studies are conducted for less than a year, and 40% of studies do not report the time since invasion of their study organism (Strayer et al 2006).…”
Section: Introductionmentioning
confidence: 99%